MAIN MEANS OF CREATING AND DEVELOPING INCLUSIVE ROUTES - Ruban, M.; Ivasenko, V.; Pavlenko, T. (Municipal economy of cities. Series: «Economy science», 2024)
The article considers the problem of creating and developing inclusive routes. It analyses current trends in this field, including the impact of technology and sociocultural changes, classifies the requirements for the design of inclusive routes, and defines the main groups of elements and means of arranging inclusive routes. The study of barrier-free environments is an essential component of the work of many academics and researchers in inclusion and accessibility. Developing a barrier-free environment is a necessary need of modern times and a powerful catalyst for the progress of any country. Barrier-free access opens up new opportunities for the active participation of many people in public life who couldn’t fully use their potential before, which is especially true for less mobile population groups and persons with disabilities, particularly. The authors have studied and classified the requirements for the arrangement of inclusive routes, addressing the needs of population groups with reduced mobility, and determined the main criteria and priorities: accessibility, informativeness, safety, and convenience. The defined advantages of inclusive routes are: inclusion and integration – inclusive routes contribute to a more inclusive society where all people have the opportunity to move freely and participate in different aspects of life; improving the quality of life – access to inclusive routes facilitates the daily movements of people with disabilities and improves their quality of life; economic advantages – the creation of inclusive routes contributes to the development of local economies and increases the attractiveness of the region for tourists and investors; social interaction – inclusive routes unite different population groups and support social interaction and mutual understanding. Considering and analysing the main groups of elements and means of developing inclusive routes will allow for determining the main calculation parameters in further studies of inclusive routes.